The Emergence and Stability of Political Family Networks (PFNs) in Banten Province, Indonesia - Yusdinur; Rochman Achwan; Indera Ratna Irawati Pattinasarany (Technium Social Sciences Journal, 2024)
The emergence of political family networks (PFNs) is an anomaly in Indonesian democracy post-New Order authoritarianism. This article discusses the emergence of political family networks in Banten Province, Indonesia, and how they maintained stability and stayed in power for over two decades. The research data, crucial for our comprehensive understanding, were collected through rigorous, in-depth interviews with key informants in Banten. Observation and study of documents were also carried out during the process of collecting data in the field. The result of the study shows that in the two decades since the 1998 democratic transition, as many as five PFNs emerged and existed in Banten Province. However, the role of local strongman Tubagus Chasan Shohib, who leveraged his social and political influence, became the most intriguing aspect of this study. His influence was critical in this region’s emergence and consolidation of PFNs. Stability in the political arena was built through the strengthening of social bonds and transactional, as well as the spread of institutions in a mimetic, normative, and coercive manner.